COOPERATIVE ROUTING FOR IMPROVING THE LIFETIME OF WIRELESS AD-HOC NETWORKS - Unnikrishnan, Aiswarya; Das, Vimal (International journal of advances in signal and image sciences, 2022)
In Wireless Ad-hoc Networks (WANET), route detection is the main issue. In the usual route detection method, the sender itself discovers the route to the receiver based on the shortest path. In this path, the sender node does not require knowledge of the in-between nodes, and the sender node transmits the information to the in-between nodes. The in-between nodes transmit the data to the near node that receives it. This procedure will be maintained till the information reaches the receiver node. The main disadvantage of usual route detection is that the node is highly moved; thus, the transmitted data packet will be dropped. A Cooperative Routing for Improving Lifetime (CRIL) in WANET is introduced to solve these issues. This approach aims to enhance the WANET lifetime and minimize the cost of route discovery. This approach uses the fresher encounter algorithm with energy-efficient routing to improve network lifetime. It is a simple algorithm to efficiently discover the routes in WANET.